10th AIAA Aviation Technology, Integration, and Operations (ATIO) Conference 2010
DOI: 10.2514/6.2010-9116
|View full text |Cite
|
Sign up to set email alerts
|

Predictability of Top of Descent Location for Operational Idle-Thrust Descents

Abstract: To enable arriving aircraft to fly optimized descents computed by the flight management system (FMS) in congested airspace, ground automation must accurately predict descent trajectories. To support development of the trajectory predictor and its uncertainty models, commercial flights executed idle-thrust descents at a specified descent speed, and the recorded data included the specified descent speed profile, aircraft weight, and the winds entered into the FMS as well as the radar data. The FMS computed the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 8 publications
0
25
0
Order By: Relevance
“…The polynomial approximation approach was very similar to a previous paper by the same author [9]. Analysis of actual TOD locations extracted from operational data [10] indicated that the TOD path distance can be approximated well by a linear function in cruise and descent altitudes, descent CAS, wind, and aircraft weight. This prompted a second look at the FMS predictions of TOD location, focusing this time on models linear in descent speed and aircraft weight.…”
Section: Introductionmentioning
confidence: 55%
See 1 more Smart Citation
“…The polynomial approximation approach was very similar to a previous paper by the same author [9]. Analysis of actual TOD locations extracted from operational data [10] indicated that the TOD path distance can be approximated well by a linear function in cruise and descent altitudes, descent CAS, wind, and aircraft weight. This prompted a second look at the FMS predictions of TOD location, focusing this time on models linear in descent speed and aircraft weight.…”
Section: Introductionmentioning
confidence: 55%
“…Stell [10] analyzed operational data for the Airbus 320 family and the B757. To keep absolute error in TOD location less than 5 nmi, the ground predictor must use accurate values of descent speed and weight for all four of these aircraft types, although nominal weight might be acceptable for the B757.…”
Section: Discussionmentioning
confidence: 99%
“…As an example, there can be an error on the order of a few nautical miles between the Flight Management System's (FMS) predicted and actual TOD point. 15 Additionally, depending on the airspace class, aircraft in level flight can pass over another level aircraft 1,000 feet below and be perfectly legal and safe. It is only when aircraft are transitioning altitudes that detections in the vertical plane become a concern.…”
Section: Introductionmentioning
confidence: 99%
“…This paper shows results of analyzing over 50 of these descents, which is a superset of the 11 analyzed in Coppenbarger, Mead, and Sweet [1]. This set of descents has two advantages over the operational data from Denver analyzed by Stell [2]:…”
Section: Introductionmentioning
confidence: 99%